2016
DOI: 10.1016/j.cbi.2015.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen hepatotoxicity and sterile inflammation: The mechanism of protection of Chlorogenic acid

Abstract: Acetaminophen hepatotoxicity is characterized by extensive necrotic cell death and a sterile inflammatory response. A recent report suggested that a therapeutic intervention with chlorogenic acid, a dietary polyphenolic compound, protects against acetaminophen-induced liver injury by inhibiting the inflammatory injury. The purpose of this letter is to discuss a number of reasons why the protective mechanism of chlorogenic acid against acetaminophen hepatotoxicity does not involve an anti-inflammatory effect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Remarkably, Zheng, Sheng, Lu, and Ji (2015) demonstrated that 5-CQA exerted a therapeutic detoxification effect against AP-induced mouse hepatic damage through the TLR3/4 and NF-κB inflammation signaling pathway. However, Jaeschke (2016) pointed out that there should be no inflammatory injury after AP administration based on the studies by Zheng et al (2015), and the underlying mechanism of 5-CQA against AP hepatotoxicity does not involve the anti-inflammatory effect. Additionally, Jaeschke (2016) suggested that 5-CQA probably affects the formation of active metabolites, since Zheng et al (2015) treated the mice at 1 hr after the AP-induced injury.…”
Section: Hepatoprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, Zheng, Sheng, Lu, and Ji (2015) demonstrated that 5-CQA exerted a therapeutic detoxification effect against AP-induced mouse hepatic damage through the TLR3/4 and NF-κB inflammation signaling pathway. However, Jaeschke (2016) pointed out that there should be no inflammatory injury after AP administration based on the studies by Zheng et al (2015), and the underlying mechanism of 5-CQA against AP hepatotoxicity does not involve the anti-inflammatory effect. Additionally, Jaeschke (2016) suggested that 5-CQA probably affects the formation of active metabolites, since Zheng et al (2015) treated the mice at 1 hr after the AP-induced injury.…”
Section: Hepatoprotectionmentioning
confidence: 99%
“…(2015), and the underlying mechanism of 5‐CQA against AP hepatotoxicity does not involve the anti‐inflammatory effect. Additionally, Jaeschke (2016) suggested that 5‐CQA probably affects the formation of active metabolites, since Zheng et al. (2015) treated the mice at 1 hr after the AP‐induced injury.…”
Section: Beneficial Properties For Healthmentioning
confidence: 99%
“…Acetaminophen is a hepatotoxic agent on overdose that is known to cause rapid cell death and damage in an inflammatory response. Chlorogenic acid, which is a compound in foods, was observed to safeguard hepatic damage and exhibits an anti‐inflammatory effect (Jaeschke, ). The enzymes involved in the arachidonic acid mechanism are reported to have preventive activities against the disease related to a neural complication, respiratory disorders, hepatic injury and gastric lesions (Yarla et al ., ).…”
Section: Natural Productsmentioning
confidence: 99%
“…Chlorogenic acid (CGA, C 16 H 18 O 9 ) is a dietary polyphenol derived from coffee, apple, blueberry, tea and some natural medicines with multiple biological activities. Growing evidence has proved the protective effect of CGA on acetaminophen hepatotoxicity which involves multiple mechanisms including antioxidation, anti-in ammatory and anti-apoptosis [25][26][27][28]. More speci cally, they are concerned with attenuating liver mitochondrial injury and reducing mitochondrial HSP60 release, activating Nrf2 antioxidative signaling pathway, inhibiting MAPK signaling pathway, inhibiting CYP2E1 and CYP1A2 enzymatic properties and suppressing TLR3/4 and NF kappa B signaling pathway [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has proved the protective effect of CGA on acetaminophen hepatotoxicity which involves multiple mechanisms including antioxidation, anti-in ammatory and anti-apoptosis [25][26][27][28]. More speci cally, they are concerned with attenuating liver mitochondrial injury and reducing mitochondrial HSP60 release, activating Nrf2 antioxidative signaling pathway, inhibiting MAPK signaling pathway, inhibiting CYP2E1 and CYP1A2 enzymatic properties and suppressing TLR3/4 and NF kappa B signaling pathway [25][26][27][28][29][30][31]. It's well known that mitophagy defect can perturb mitochondrial function and cause progressive accumulation of reactive oxide species (ROS) and the inability to supply energy, leading to oxidative stress, sterile in ammation and cell apoptosis, reinforcing a vicious cycle.…”
Section: Introductionmentioning
confidence: 99%